The road to net zero in a renewable energy-dominated electricity system: Impact of EV charging and social cost of emission on the optimal economic dispatch - Malolan Sundararaman; Balasubramanian Sambasivam (Green Energy and Intelligent Transportation)
This study explores the intersection of two pivotal interventions aimed at achieving carbon neutrality: the electric vehicles (EVs) adoption and the renewable energy (RE) electricity generation. Focusing on a Renewable Energy-Dominated (RED) electricity system, the research examines the interdependence between these interventions and their collective impact on economic dispatch. The study's objective is to determine optimal economic dispatch strategies that meet hourly electricity demand, considering two distinct supply scenarios across eight supply options. The first scenario assesses the maximum possible supply, while the second contemplates the minimum possible supply from each option. Additionally, the study delves into the influence of social cost of emissions on these economic dispatches. Employing an experimental design, the study generates representative load curves that incorporate EV charging demands for varied levels of EV penetration, alongside regular electricity demand. Data from Karnataka's RED electricity system provides a basis for the supply-side analysis. The economic dispatch for each supply scenario is formulated as a Mixed Integer Linear Program (MILP), aiming to minimize both costs for generation and social costs of emissions, while adhering to operational constraints of the supply options. Key findings from this approach, highlight several critical insights: the significant role of incorporating social costs in economic dispatch decisions, the tangible impact of EV demand on supply shortages, and the importance of maintaining supply capacity to minimize these shortages.